Anion–π Catalysis of Enolate Chemistry: Rigidified Leonard Turns as a General Motif to Run Reactions on Aromatic Surfaces. (24th February 2016) - Cotelle, Yoann; Benz, Sebastian; Avestro, Alyssa‐Jennifer; Ward, Thomas R.; Sakai, Naomi; Matile, Stefan
Abstract: To integrate anion–π, cation–π, and ion pair–π interactions in catalysis, the fundamental challenge is to run reactions reliably on aromatic surfaces. Addressing a specific question concerning enolate addition to nitroolefins, this study elaborates on Leonard turns to tackle this problem in a general manner. Increasingly refined turns are constructed to position malonate half thioesters as close as possible on π‐acidic surfaces. The resulting preorganization of reactive intermediates is shown to support the disfavored addition to enolate acceptors to an absolutely unexpected extent. This decisive impact on anion–π catalysis increases with the rigidity of the turns. The new, rigidified Leonard turns are most effective with weak anion–π interactions, whereas stronger interactions do not require such ideal substrate positioning to operate well. The stunning simplicity of the motif and its surprisingly strong relevance for function should render the introduced approach generally useful.